Pengaruh Model Pembelajaran Blended Learning Terhadap Hasil Belajar PKN Siswa Kelas V SD Negeri 101731 Kampung Lalang T.A 2023/2024 - Rahmi, Rizki Aslia; Ramadhan, Nuri; Ramadhani, Mastari (Medan Resource Center, 2024)
This research employs a descriptive qualitative method, aiming to uncover the reality of the influence of school facilities and infrastructure on enhancing the learning motivation of fifth-grade students at UPT SPF SD Negeri 104202 Bandar Setia, Percut Sei Tuan District, Deli Serdang Regency. The research subjects consisted of 30 fifth-grade students, and the study was conducted over six sessions. The benchmarks in this research include the availability of standard educational facilities such as classrooms, sports areas, worship spaces, libraries, laboratories, playgrounds, and other learning resources that support the learning process, including the use of information and communication technology. Hypothesis testing results show that the calculated r-value (rtcount) = 0.484 is greater than the r-value from the r-distribution table (rtable) = 0.361 with a 5% significance level (rttable < rcount). This indicates that H1 is accepted, confirming a significant influence of school facilities and infrastructure on increasing the learning motivation of fifth-grade students at the mentioned school.